DAMPAK APLIKASI INSEKTISIDA PERMETRIN TERHADAP SERANGGA HAMA (THOSEA SP.) DAN SERANGGA PENYERBUK (ELAEIDOBIUS KAMERUNICUS) DALAM AGROEKOSISTEM KELAPA SAWIT - Rosma Hasibuan, I Gede Swibawa, Agus M. Hariri, Sudi Pramono, F.X. Susilo1, dan Nurafiah Karmike (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2002)
Impact of Permethrin-Insecticide Application on Insect Pest (Thosea sp.) and Insect Pollinators (Elaeidobius kamerunicus) in Oil Palm Agroecosystem. Insecticide efficacy studies are usually determined from the target insect (pest) data without regard to the effect of that treatment on the non-target insects (such as pollinators). This study examined the effect of permethrin (one of widely used insecticides for agriculture) on defoliating insect pest (nettle caterpillar, Thosea sp.) and insect pollinator (weevil, Elaeidobius kamerunicus) which lives on pollen of male oil palm flowers. A complete block design was used in which each of four blocks consisted of 5 treatments (4 concentrations of permethrin; 50; 100; 200; and 250 ppm and control) . The results clearly demonstrated that the application of permethrin reduced significantly the number of nettle caterpillar throughout all sprayed plants (up to 100% 14 d after treatments). A significant difference in mean population of the caterpillar were detected between plots sprayed with permethrin (0.05; 0.25; 0.53; and 2.00 larvae/leaves at concentrations of 250; 200; 100; and 50 ppm respectively) and control plant (5.2 larvae/leaves) 3 d after treatments. This insecticide effects persisted for at least 14 d after treatments. On the other hand, permethrin application in oil palm agroecosystem had adverse effects on main pollinator (E. kamerunicus). The number of weevil pollinators on sprayed plants (12.5; 59.3; 77.5; and 209.5 weevil/male flower at concentrations of 50; 100; 200; and 250 ppm respectively) were significantly fewer compared to the control plants (976.0 weevil/male flower). The results indicate that, despite high efficacy of permethrin in reducing number of insect pests of oil palm (Thosea sp.), its application also cause a severe impact on important insect pollinators (E. kamerunicus).